Baffled clarification basin hydrodynamics and elution in a continuous time domain - Li, Haochen; Spelman, David; Sansalone, John (Journal of hydrology (Amsterdam), 2021)
[Display omitted] •A large clarifier basin retrofit is monitored and modeled for unsteady tracer fate.•The retrofit consisted of permeable baffles to modify basin hydrodynamics.•Results indicate basin volume and mean flow metric not representative guidance.•Retrofit improved short-circuiting and volume utilization of same bathymetry.•Proposed CFD model extended for basin forensics and to retrofit alternatives. Clarification basins have been implemented for millennia as a unit operation (UO). Modern basins are intended to manage hydrologic/hydraulic phenomena while sequestering particulate matter (PM) and PM-bound constituent loads. Water treatment systems, subject to steady flows, have used baffles to modulate dead zones, residence time and hydrodynamics. Yet, permeable baffling impacts to larger-scale basin hydrodynamics subject to highly unsteady continuous time domain flows is a novel investigation. In this study, in situ monitoring and numerical simulations are conducted for a full-scale prototype urban drainage basin, while geometrically oversized with respect to the relatively coarse particle size distribution and hydraulic loading, retrofitted with gabion baffles composed of crushed carbonated recycled concrete. A 40-day tracer monitoring of hydrodynamics within the retrofit basin is tested against a novel application of a depth-averaged unsteady Reynolds-averaged Navier-Stokes equations (URANS) as a computational fluid dynamics (CFD) model in the OpenFOAM framework. A dual-peak elution pattern is observed in response to tracer injections in the physical and simulated (fully transient and quasi-steady) results. Short-circuiting around the baffles in the as-built retrofit is elucidated with monitoring and modeling. Simulations of retrofit configurations (pre-retrofit, as-designed, as-built and impervious baffles) indicate, in comparison to the pre-retrofit, a well-baffled system reduces short-circuiting, delays elution, and improves PM separation. Permeable baffles provide hydrodynamic benefits as compared to impervious baffles. The novel application of this depth-averaged URANS CFD model accommodates complex geometry and physics; and elucidates contrasting Reynolds number distributions of inter- and intra-baffle flows. The CFD model with continuous time domain flows is a viable tool for design, analysis, permitting and management of basins with or without baffle retrofits. The model extends insights beyond analytical tools and complements tools such as the SWMM (Stormwater Management Model).